HUBUNGAN KETERJANGKAUAN MAKANAN TERHADAP PRESTASI BELAJAR MAHASISWA - Astin Tono; Faurina Risca Fauzia (JOURNAL HEALTH AND NUTRITIONS, 2022)
Pocket money, food prices, and meal program assistance all contribute to the affordability of eating. This factor will influence the consumption of unhealthy foods. Food consumption is one of the factors that reduce productivity, particularly in learning performance. Student achievement is an important factor in determining students' future success. This study aims to determine the relationship between food affordability and student achievement in Lampung. This study employed a quantitative method, which was included in the category of empirical observational analytic research with a cross-sectional design. The sampling technique used in this study was snowball sampling, and the sample size was 196 active students in Lampung. Food affordability was collected through a questionnaire, while learning achievement was collected through the value of the GPA (Student Cumulative Index) in the previous year, and the analysis used in this study was the Analysis of the Independent Sample T-Test test. The findings revealed that there was no relationship between food affordability and learning achievement. These findings can be seen in the calculation of the independent t-test test results; if the indicator of food expenditure is P 0.064 > 0.05, purchasing power is P 0.96 > 0.05, and food program assistance is P 0.24 > 0.05, then Ho is accepted as indicating no relationship. Indicators of food expenditure, purchasing power, and food program assistance show no relationship between eating affordability and learning achievement. It is hoped that students will choose to eat according to balanced nutrition guidelines in order to focus more on receiving the material provided and thus improve their achievement.Komponen keterjangkuan makan terdiri uang saku, harga makanan dan bantuan program makan. komponen ini di akan mempengatuhi asupan makan yang tidak sehat. asupan makanan menjadi salah satu faktor menurunya produktivitas terutama pada perfoma belajar. Prestasi belajar mahasiswa merupakan salah satu faktor penting dalam kesuksesan mahasiswa dimasa depan. Penelitian ini adalah mengetahui hubungan keterjangkauan makanan terhadap terhadap prestasi mahasiswa di lampung. Penelitian ini dengan metode kuantitatif yang termasuk jenis penelitian empirik observasional analitik dengan desain cross sectional. Teknik sampling  yang di gunakan pada penelitian ini menggunakan snowball sampling, jumlah sampel dalam penelitian ini sebanyak 196 mahasiswa aktif di kota lampung. Pengumpulan keterjangkauan makan di peroleh dari kuesioner, sedangkan untuk prestasi belajar diperoleh dengan nilai IPK (Indeks Kumalatif Mahasiswa) satu tahun terakhir dan analisis ini yang di gunakan dalam penelitian ini adalah Analisis uji Independent Sample T-Test. Hasil Penelitian menunjukkan bahwa Tidak ada hubungan keterjangkauan makan dengan prestasi belajar. hasil ini bisa di lihat dari perhitungan Hasil uji Independet t-test di ketahui indikator pengeluaran untuk makan P 0,064 > 0,05, Daya beli P 0,96> 0,05, dan bantuan program makan P 0,24> 0,05, maka Ho diterima menunjukkan tidak ada hubungan. Komponen keterjangkauan makan tidak berhubungan dengan prestasi belajar baik dari indikator Pengeluaran Makan, Daya Beli dan bantuan program makan. Harapannya Mahasiswa Memilih makan sesuai dengan pedoman gizi seimbang membantu lebih berkosentrasi dalam menerima materi  yang di berikan sehingga dapat meningkatkan prestasi.